Vulnerability to flooding of the towns of Mabitac and Santa Maria, Laguna, Philippines - Pati, Romeo C; Franco, Danielito T.; Alcantara, Antonio J. (2014)
The combination of flood modelling and socio-rconomic was used to determine the flood vulnerability of the towns of Santa Maria and Mabitac, Laguna, Philippines. Geographic Information System (GIS)-hazard mapping and vulnerability-resilience indicator were used to assess the interaction of a flood hazard and the socio-economic conditions of the people in the area. The Hydrologic Engineering Center for Hydrologic Modelling System (HEC-HMS) and Hydrologic Engineering Center's River Analysis Systen (HEC-RAS) modelling system was to derive the synthetic hydrograph and delineated the inundated areas in the flood-prone barangays (village) of Santa Maria and Mabitac. The flood modlling predicted the flood depths in seven out of ten communities and delineated the inundated barangays of the two towns. The social vulnerability analysis indicated that Barangays (village) Jose Rizal, Masinao, Adia and Coralan in Santa Maria and Barangays San Antonio, Libis ng Nayon, Bayanihan, Pag-asa, Nanguma and Lambac in Mabitac are very vulnerable to flooding. The study revealed environment-related aspects that are helpful in reducing the impacts of flooding such as, strengthening the flood warning system and emergency response capacity through flood hazard zonation mapping and rehabilitation of the watershed in Santa Maria.
Keywords: Flood prevention